Energy Emissions from Failure Phenomena: Mechanical, Electromagnetic, Nuclear - Carpinteri, A.; Cardone, F.; Lacidogna, G. (Experimental mechanics, 2010)
Characterizing the nature of the different forms of energy emitted during compressive failure of brittle materials is an open and debated argument in the scientific literature. Some research has been already conducted on this subject in the scientific community based on the signals captured by the acoustic emission measurement systems. On the other hand, there are not many studies yet about the emission of electromagnetic charge, and for the first time we are talking about piezonuclear neutron emissions from very brittle failure of rocks specimens in compression. The authors analyze these three different emissions from an experimental point of view.